Analysis of agricultural policy and agreements of Havana (2016)
This paper analyzes the agricultural public policies of the President Santos administration through the analysis of three documents that can be considered as instruments of public policy. The background and importance of the rural sector are presented and a comparison of the agricultural component between the 2010-2014 and 2014-2018 development plans corresponding to the two presidential periods of Juan Manuel Santos is presented. The report "The Colombian Field: A Road to Peace and Well-being" is also analyzed, a document that is the final report of the Mission for Field Transformation carried out by the National Planning Department.